2019
DOI: 10.1109/tvcg.2019.2898820
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Fine Roughness Perception of Vibrotactile Textured Surface using Pseudo-haptic Effect

Abstract: Fig. 1. Our proposed method modulates the fine roughness perception of vibrotactile textured surfaces using pseudo-haptic effect. Our user study showed that users felt the surface rougher in response to a parameter configuration of visual feedback.Abstract-Playing back vibrotactile signals through actuators is commonly used to simulate tactile feelings of virtual textured surfaces. However, there is often a small mismatch between the simulated tactile feelings and intended tactile feelings by tactile designers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…As for texture perception, some studies attempted to generate texture perception using the pseudo-haptic effects without sophisticated haptic devices [1,2,5,9,10]. Previously, we proposed a pseudo-haptic method for modulating the vibrotactile roughness of virtual surfaces during pen-surface interactions, and our user study showed the effectiveness of the proposed method [9]. In the method, users watched a visually perturbed contact point.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…As for texture perception, some studies attempted to generate texture perception using the pseudo-haptic effects without sophisticated haptic devices [1,2,5,9,10]. Previously, we proposed a pseudo-haptic method for modulating the vibrotactile roughness of virtual surfaces during pen-surface interactions, and our user study showed the effectiveness of the proposed method [9]. In the method, users watched a visually perturbed contact point.…”
Section: Introductionmentioning
confidence: 86%
“…This study adopted the same pseudo-haptic method using visual oscillation as [9]. Please see details there.…”
Section: Pseudo-haptic Methods Using Visual Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the visual appearance of the visual object often provides illusory haptic sensations to the users manipulating the object. For example, previous studies have shown that pseudo-haptic feedback can modulate the perception of virtual spring compliance ( Lécuyer et al, 2000 ), friction ( Lécuyer et al, 2000 ; Ujitoko et al, 2019a ), object edge angle ( Ban et al, 2012 ), mass ( Dominjon et al, 2005 ; Issartel et al, 2015 ; Yu and Bowman, 2020 ), weight ( Brewster et al, 2019 ), and texture ( Ujitoko et al, 2019b ; Sato et al, 2020 ). A key principle of pseudo-haptic feedback is the spatio-temporal dissociation of vision, haptics, proprioception, and motor control.…”
Section: Introductionmentioning
confidence: 99%
“…So far, pseudo-haptic feedback has been studied in situations, where a user manipulates a virtual object (e.g., a cursor) by operating a computer mouse ( Lécuyer et al, 2004 ; Dominjon et al, 2005 ; Kumar et al, 2017 ), tablet PCs ( Ujitoko et al, 2015 ; Costes et al, 2019 ), pen devices ( Ujitoko et al, 2019a , b ), virtual hands ( Sato et al, 2020 ), real objects ( Brewster et al, 2019 ), and mixed reality technologies ( Ban et al, 2012 ; Issartel et al, 2015 ; Kawabe, 2020 ). The use of these devices involves hand movements that are more or less consistent in direction with the movement of the virtual object.…”
Section: Introductionmentioning
confidence: 99%